2015
DOI: 10.17221/8522-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green alga Planktochlorella nurekis on selected bacteria revealed antibacterial activity in vitro

Abstract: ABSTRACT:The green alga Planktochlorella nurekis (Chlorellaceae, Chlorophyta) is considered a producer of antibacterial mixture of long-chain fatty acids, which has possibly similar composition and mode of action as chlorellin produced by another green alga, Chlorella vulgaris. Although the antibacterial properties of C. vulgaris have been reported, the interactions of P. nurekis with bacteria have not been determined yet. The aim of this study was to elucidate the effect of P. nurekis water suspension on grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
(28 reference statements)
2
7
0
Order By: Relevance
“…The fatty acid concentrations obtained in the study by Cermak L. et al (2015) on P. nurekis biomass are significantly lower than in the case of biomass obtained from polyploid clones P. nurekis subject of our analyses. These differences concern the content of myristic acid whose content in P. nurekis biomass is estimated at 1.74%, palmitic acid at 26.91% and linoleic acid (omega 6) at 4.13% [ 4 ]. In the case of biomasses obtained from polyploid clones, the content of these acids increases significantly to 5.1%, 61.1% and 31.2%, respectively (characteristics of the FA profile of biomasses are described in an earlier paper [ 15 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fatty acid concentrations obtained in the study by Cermak L. et al (2015) on P. nurekis biomass are significantly lower than in the case of biomass obtained from polyploid clones P. nurekis subject of our analyses. These differences concern the content of myristic acid whose content in P. nurekis biomass is estimated at 1.74%, palmitic acid at 26.91% and linoleic acid (omega 6) at 4.13% [ 4 ]. In the case of biomasses obtained from polyploid clones, the content of these acids increases significantly to 5.1%, 61.1% and 31.2%, respectively (characteristics of the FA profile of biomasses are described in an earlier paper [ 15 ]).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of biomasses obtained from polyploid clones, the content of these acids increases significantly to 5.1%, 61.1% and 31.2%, respectively (characteristics of the FA profile of biomasses are described in an earlier paper [ 15 ]). Additionally, the inhibitory activity of biomass on the growth of microorganisms in the work of Cermak L. et al (2015) [ 4 ] was demonstrated at higher concentrations, i.e., 6 mg·mL −1 observed against Escherichia coli , Salmonella enterica var. infantis K2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell walls of both bacteria were perforated, resulting in rupture of the cell wall, cytoplasmic leakage, shrinking of the protoplasm, cytoplasmic vacuolation, scattering of chromatin, distortion of the outer cell shape, and decreased cell size. Čermák et al [ 44 ] reported the antibacterial long-chain fatty acids in the green microalga Planktochlorella nurekis to be significant inhibitors of Campylobacter jejuni , Escherichia coli , Salmonella enterica var. Enteritidis , Salmonella enterica var.…”
Section: Mechanisms Of Pharmacological Action and Potential Applicmentioning
confidence: 99%